WORD FORMATION PROCESSES OF AUTOMOTIVE JARGONS IN AUTOWEEK MAGAZINE - WINARNI, DEFRINA INDRA (Jurnal Ilmiah Mahasiswa FIB, 2013)
People create certain terms related to certain activities called jargon. One of the activities popular today is automotive activities. People begin tocreate and use meaningful language containingwords variation related to automotive activities.Jargons have close relationship with morphological aspect that is called word formation process. Word formation process is the process of designing new words and renovating new senses of old words. The writer conducted the study on word formation processes of automotive jargons found in Autoweek Magazine. This study is conducted to reveal what word formation processes of automotive jargons found in Autoweek Magazine and to find out the meaning of automotive jargons.This study used a document analysis as the research method since it described the word formation processes of automotive jargons in Autoweek Magazine published on February 18th, 2013. Specifically, the writer took the opening article namely "START" that contains six topics in sub articles.This study reveals thatmost of the automotive jargons undergoe with the compounding processes. Those processes of compounding are characterized by joining two words and making new terms. There are 24 out of 35 automotive jargons shaped by compounding processes. Then 5 out of 35 automotive jargons are shaped using acronym process, 2 out of 35 automotive jargons are formed using derivation processes, 2 out of 35 automotive jargons are shaped using invention or coinage processes, 1 out of 35 automotive jargons undergoes the process of borrowing, and the last 1 out of 35 automotive jargons undergoes the process of clipping.The writer suggests further researchers tostudyword formation process and analyzethe articles in AutoweekMagazine or other automotive magazines,therefore the automotive jargons can be seen in more types of word formation processes.  Keywords:Word Formation Process, Automotive, Automotive Jargons, Magazine, Autoweek Magazine.